Analisis Medan Magnet dan Aplikasinya dalam Fisika Plasma - Telaumbanua, Agus Fortiman; Ndruru, Hengky Kurniawan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study discusses the role of magnetic fields in the control and utilization of plasma, focusing on its applications in nuclear fusion, industrial technology, and medicine. Magnetic fields have a significant impact on plasma behavior, affecting the movement of charged particles, plasma stability, and plasma confinement at high temperatures. In nuclear fusion, magnetic fields serve to contain plasma in tokamak and stellarator reactors, although major challenges remain concerning long-term stability and energy management. The research also reviews other technological applications, such as material deposition and microwave therapy, which utilize plasma control through magnetic fields. The findings indicate that magnetic fields are a key component in various plasma-based technologies, yet further research is needed to address technical challenges and optimize these applications.